Congruent and Metaphorical Coding Based on Grammatical Mood and Speech Function in Oprah Winfrey’s Talk Show - ., Lilian; Lubis, Syahron; ., Nurlela (KnE Social Sciences, 2019)
This research is to examine the use of Mood and Speech Function in Oprah Winfrey’s Talk Show. Oprah Winfrey’s Talk Show is chosen because it is an American syndicated talk show that aired nationally for 1986 to 2011. It is highly influential and many of its topics have penetrated into the American pop-cultural consciousness. The analysis of this research based on Eggins, S and Slade (1997:184) which includes Congruent and Incongruent Realization of Speech Function. This paper concerns on the analysis of Congruent and Incongruent of Mood and Speech Function in Oprah Winfrey’s Talk Show. This uses descriptive research method, in which the data are described systematically to get an accurate and factual result. The data used in this study are the clauses containing of grammatical mood and speech function used by Oprah Winfrey’s Talk Show. The finding describes that as a talk show host, Oprah Winfrey, has a power to express Incongruent or Metaphorical Coding in Realization of Speech Function. It also to analyze how the mood and speech function realized in the conversation in Oprah Winfrey’s Talk Show. Keywords: Congruent, Incongruent, Metaphorical Coding, Mood, Speech Function